2012
DOI: 10.1590/s0100-736x2012001000008
|View full text |Cite
|
Sign up to set email alerts
|

Situação epidemiológica da infecção por Toxoplasma gondii em equídeos na microrregião do Brejo Paraibano

Abstract: Pesq. Vet. Bras. 32(0):995-1000, outubro 2012 995 RESUMO.-Objetivou-se com o estudo caracterizar a situação epidemiológica da infecção por Toxoplasma gondii em equídeos na microrregião do Brejo Paraibano, região Nordeste do Brasil. Anticorpos contra T. gondii foram pesquisados em 257 amostras de equídeos (204 equinos, 46 muares e sete asininos) em 26 propriedades. Para o diagnóstico sorológico utilizou-se a Reação de Imunoϐluorescência Indireta (RIFI) e um ponto de corte de 1:64. O número de focos encontrado f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Alike the the present research, Oliveira et al (2012) also studied animals in Bahia and found that the sources of running water destined for consumption by equids were a risk factor for infection. In fact, water consumption on the riverside, a place also frequented by cats, is an ideal environment for sporulation of oocysts.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Alike the the present research, Oliveira et al (2012) also studied animals in Bahia and found that the sources of running water destined for consumption by equids were a risk factor for infection. In fact, water consumption on the riverside, a place also frequented by cats, is an ideal environment for sporulation of oocysts.…”
Section: Discussionsupporting
confidence: 67%
“…These differences have made it difficult to compare studies (Camossi et al, 2010;García-Bocanegra et al, 2012;Papini et al, 2015). Moreover, Oliveira et al (2012) and Papini et al (2015) pointed out that there is no gold-standard technique for making the diagnosis of infection in equids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, seropositivity varied from 5% by LAT to 8% by IFAT using the same cut off titer (50). Using a titer of 64, seropositivity varied from 1.5% of 197 [8], 28.6% of 7 [9] and 43.2% of 88 [3] donkeys from Brazil. Among the three reports from Europe, seroprevalences were 25.6% (MAT, titer 25) of 25 donkeys from Spain [6], 11% (LAT, titer 64) of 100 donkeys from Turkey in one study [12] and 62% (dye test, titer 16) of 92 donkeys from Turkey in another report [1].…”
mentioning
confidence: 99%
“…O contato com felinos, em especial o gato doméstico, é um dos principais fatores de risco para a aquisição da infecção pelo T. gondii para animais herbívoros (VIDOTTO et al, 1997;OLIVEIRA FILHO et al, 2012). A eliminação de oocistos nas fezes dos felinos pode garantir a contaminação da pastagem e da água destinada ao consumo destes animais (MACHACOVA et al, 2014).…”
Section: Discussionunclassified